Digital learning attributes and students’ academic achievement among Pakistani entrepreneurship students: Mediating role of student engagement - Faiza Aftab (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This research aims to examine the mediating role of student engagement in the connection between student achievement and characteristics of digital learning among Pakistani entrepreneurship students by combining the Social Learning Theory with the Theory of Reasoned Action. Methodology: Face-to-face survey data were collected from 450 students in Pakistani business and entrepreneurship programs. Findings: Structural Equation Modeling (SEM) findings indicate that digital competence positively affects student engagement. In addition, the findings revealed the mediating role of student engagement between digital competence, digital readiness, and e-learning attitude and their impact on student’s academic achievement in Pakistani business and entrepreneurship programs. Implications/Novel Contribution: It is possible to extrapolate the methodology used in the current study and apply it to evaluate students from different schools and countries. More investigation should examine how school administrators and teachers rate students’ dispositions toward e-learning, both in traditional classroom settings and online.